Consider a circle Ω ( x , y ) : x 2 + y 2 − 6 x − 1 2 y − 4 0 5 = 0 . Let P ≡ ( 1 3 , 2 6 ) .Let t 1 , t 2 be the tangents from P to Ω . Let t 1 , t 2 ∩ Ω = { A , B } respectively . If A ≡ ( x A , y A ) , B ≡ ( x B , y B ) ,
Find x A + y A + x B + y B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since the calculations are quite tedious , I will post only the method and not the working:
First from the equation of circle we find that center O ≡ ( 3 , 6 ) and radius r = 1 5 2 .
Let the slope of tangent be δ . So we have the equation of tangent :
y − 2 6 = δ ( x − 1 3 ) ⇒ δ x − y − 1 3 ( δ − 2 ) = 0
1 5 2 = δ 2 + 1 ∣ δ ( 3 ) − ( 6 ) − 1 3 ( δ − 2 ) ∣ After squaring both sides and some simplification we have, ⇒ ( 7 δ + 1 ) ( δ + 1 ) = 0 ⇒ δ = − 7 1 o r − 1
x 2 + y 2 − 6 x − 1 2 y − 4 0 5 x + 7 y = = 0 1 9 5
After solving , we get ( x A , y A ) = ( 6 , 2 7 ) .
x 2 + y 2 − 6 x − 1 2 y − 4 0 5 x + y = = 0 3 9
After solving , we get ( x B , y B ) = ( 1 8 , 2 1 ) .
So required sum = 6 + 2 7 + 1 8 + 2 1 = 7 2 .
Problem Loading...
Note Loading...
Set Loading...
Let a point of tangency to the circle be ( x , y ) . The tangent to the circle must be perpendicular to the line that contains the same point and the radius of the circle. The slope of a tangent will be x − 1 3 y − 2 6 and the slope of the radius-containing line is x − 3 y − 6 . Because these lines are perpendicular, we have that x − 1 3 y − 2 6 = − y − 6 x − 3 ⟶ x 2 + y 2 − 1 6 x − 3 2 y + 1 9 5 = 0 or x 2 + y 2 = 1 6 x + 3 2 y − 1 9 5 . Substituting this into the equation of the circle Ω given yields 1 0 x + 2 0 y − 6 0 0 = 0 or x = 6 0 − 2 y . Further substituting this into Ω gives us 5 y 2 − 2 4 0 y + 2 8 8 0 = 0 . The sum of the solutions to this y A + y B is 5 2 4 0 = 4 8 . Similarly, we find x A + x B = 2 4 . Therefore x A + y A + x B + y B = 7 2 .